Development of Pamukkale Piano Learning Style Scale - Serkan Demirtaş; Serhat Süral (International Journal of Assessment Tools in Education)
In musical instrument training, piano has been taught as a compulsory instrument in all departments of Music Education. It is thought that as a major instrument,  piano  plays a crucial role in music education. Without question, it is highly vital to raise individuals' awareness  of learning styles towards learning piano in effort to practice piano courses more efficiently and effectively. In this respect, the present study is of utmost importance as it will be a pioneer study and make a great deal of contributions to the relavant field. The current study was designed to develop a valid and reliable scale. The population of the study consisted of 170 music teacher candidates majoring in Music Education, including those who already took piano lessons. Although the study successfully accessed to the whole sample, only 133 scales were included to the research, however, due to inaccurate or incomplete data in subjects’ responses. To test the construct validity of the scale,  explanatory factor analysis (EFA) and confirmatory factor analysis (CFA) were used. The scale consists of  four sub-dimensions, namely, independent, analytical, dependent and affective learning styles.